2020
DOI: 10.17269/s41997-020-00425-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the decision to immunize: insights into the information needs and priorities of people who have utilized an online human papillomavirus (HPV) vaccine decision aid tool

Abstract: Setting People in Alberta are more likely to seek information about cancer prevention online than they are to have this conversation with their primary care provider. As people turn to the internet to support health decision-making, it is critical that we improve the supportiveness of the virtual health setting for cancer prevention. Intervention In 2014, the Alberta Cancer Prevention Legacy Fund launched an online HPV Decision Aid Tool to support evidence-informed decision-making in response to suboptimal upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
(15 reference statements)
1
8
0
Order By: Relevance
“…28 These issues include the prevalence of HPV, the association between HPV and cervical cancer, certain HPV types that cause cervical cancer, cervical cancer screening, and some risks and symptoms related to HPV. The information needs identified in this study were similar to results reported in studies conducted in England, 29,30 Canada, 31 and Malaysia. 32 The overlapping results support the need to provide women with information about HPV, its connection with cervical cancer, and prevention strategies.…”
Section: Discussionsupporting
confidence: 84%
“…28 These issues include the prevalence of HPV, the association between HPV and cervical cancer, certain HPV types that cause cervical cancer, cervical cancer screening, and some risks and symptoms related to HPV. The information needs identified in this study were similar to results reported in studies conducted in England, 29,30 Canada, 31 and Malaysia. 32 The overlapping results support the need to provide women with information about HPV, its connection with cervical cancer, and prevention strategies.…”
Section: Discussionsupporting
confidence: 84%
“…Online participation in some programmes (via mobile application) was credited as a facilitator to programme implementation and delivery due to ease of accessibility52 and ability to connect asynchronously in real-world settings 53. In one case, a programme was provided through a mobile application that had an existing large number of users 54…”
Section: Resultsmentioning
confidence: 99%
“…50 Finally, programmes that do not require a large time commitment from both those delivering the programme and participants may be more successful in their objectives. 51 Online participation in some programmes (via mobile application) was credited as a facilitator to programme implementation and delivery due to ease of accessibility 52 and ability to connect asynchronously in realworld settings. 53 In one case, a programme was provided through a mobile application that had an existing large number of users.…”
Section: Programme Delivery Teammentioning
confidence: 99%
“…Parents/guardians often have insufficient or inadequate information about the HPV vaccine [6,[9][10][11][12][13]; this issue can be exacerbated by language barriers, which may prevent full understanding of immunization program materials [9,20,22]. Some parents/guardians are apprehensive about the safety of the HPV vaccine [6,[10][11][12][13][14][15][16][17]. There is significant concern from parents/guardians regarding HPV's connection to sexual activity.…”
Section: Introductionmentioning
confidence: 99%